The role of education in the worldview of dialectical materialism for Vietnamese students today - Phạm Bá Thịnh; Nguyễn Thị Duyên (Tạp chí Nghiên cứu Khoa học Công đoàn, 2022)
Focusing on clarifying the necessary to equip Vietnamese students with dialectical materialistic worldview; specific characteristics, connotation of dialectical materialistic worldview and the role of education of dialectical materialist worldview for students